The Brain Gain of Corporate Boards: Evidence from China - GIANNETTI, MARIASSUNTA; LIAO, GUANMIN; YU, XIAOYUN (Journal of Finance, 2015)
ABSTRACT We study the impact of directors with foreign experience on firm performance in emerging markets. Using a unique data set from China, we exploit the introduction of policies to attract talented emigrants and increase the supply of individuals with foreign experience in different provinces at different times. We document that performance increases after firms hire directors with foreign experience and identify the channels through which the emigration of talent may lead to a brain gain. Our findings provide evidence on how directors transmit knowledge about management practices and corporate governance to firms in emerging markets.